Evaluation of plant extracts for the control of fungal diseases of mulberry - and R.K. DATIA, H.S. SARVAMANGALA, GOVINDAIAH (Indian Phytopathology, 2002)
Antifungal activity of leaf extracts of Azadirachta indica, Calotropis gigantea, Catharanthus roseus, Eucalyptus sp., Parthenium hysterophorus and Pongamia pinnata was tested against Cerotelium fici and Cercospora moricola causing leaf rust and leaf spot diseases in mulberry, respectively. A. indica was more effective inhibiting spore germination of C. fici by 91.2 per cent, whereas extracts of Eucalyptus sp. and C. gigantea proved highly toxic to C. moricola inhibiting conidial germination by 91.5 and 91.3 per cent, respectively. Under field conditions also, leaf extracts of Eucalyptus sp. and C. gigantea showed promising results reducing leaf spot disease incidence by 63.6 and 56 per cent, respectively. Extract of P. pinnata showed poor fungitoxicity against both the fungi tested.